TANGGUNG JAWAB PELAKU USAHA PENJUAL APLIKASI BERBAYAR TERHADAP PROMOSI YANG MENYESATKAN - Raldi Sembiring Meliala; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Along with the rapid development of science and technology in the modern era, it hasresulted in increasing public demand for services providing goods/services consumed by thepublic. This creates many opportunities for business actors to meet demand for these goodsand services. Buying and selling in this modern era is not only limited to in person but can bedone online, which makes it easier for many business people to run their business.However, in reality, many business actors engaged in online buying and selling do not carryout their rights and obligations properly, which puts consumers in a weak and disadvantagedposition. One of them is the business actor @booming_market which is engaged in buyingand selling netfix accounts. @booming-market business actors carry out ambiguous andmisleading promotions in order to reap maximum profits by not being honest and transparentwith their consumers. the aim of this thesis research is first, to analyze the responsibility of@booming-market business actors towards consumers who are harmed by misleadingpromotions. Second, analyze the forms of legal action that can be taken by @booming-market consumers who are harmed by misleading promotions.From the research results it can be concluded that. First, as regulated in Article 19 UUPK,@booming-market business actors are responsible for providing compensation for consumerlosses. Second, there are 2 legal remedies that can be taken by consumers, namely throughlitigation and non-litigation, but in this case there is a risk that the agreement can be canceledby law because it does not meet the objective requirements for the validity of an agreementbecause the Netflix company has prohibited it from selling. buy back the netflix account. Theauthor's advice is: First, consumers should understand more about consumer rights so thatthey can make careful considerations before deciding to consume a good/service. Second,business actors who promote a product must provide correct information about the product.The advertising content must not contain misleading information or make uncertain promises.You should comply with statutory regulations and not shy away from your responsibilities asa business actor.